FACTORS AFFECTING PAYOUT RATIO DIVIDENDS WITH FOREIGN OWNERSHIP AS MODERATING VARIABLES IN MANUFACTURING COMPANIES IN INDONESIA STOCK EXCHANGE - Arfianny, Arfianny (International Journal of Public Budgeting, Accounting and Finance, 2020)
The purpose of this research is to find out and analyze the factors that influence Dividend Payment Ratios such as Return On Assets, Debt to Equity Ratio, Asset Growth, Free Cash Flow and Company size partially and simultaneously to the dividend payment ratio of manufacturing companies on the Indonesia Stock Exchange . This study also aims to determine the effect of foreign ownership variables on the factors that influence dividend payout ratios. The population of this research is 35 manufacturing companies on the Indonesia Stock Exchange with manufacturing years 2015 to 2017. The research sample was selected using the purposive sampling method. Data were processed using panel data regression statistical test methods. The results of this study indicate that return on assets, debt to equity ratio, asset growth, free cash flow and firm size simultaneously influence the dividend payout ratio. Partially the return on asset variable has a positive and significant effect on the dividend payout ratio and the firm size variable has a negative and significant effect on the dividend payout ratio of manufacturing companies on the Indonesia Stock Exchange. While debt to equity ratio, asset growth and free cash flow do not significantly influence the dividend payout ratio of manufacturing companies on the Indonesia Stock Exchange.